THE EFFECT OF TAXPAYER AWARENESS ON MOTOR VEHICLE TAXPAYER COMPLIANCE WITH TAX SOCIALIZATION AS A MODERATING VARIABLE - Dewantari, Aliya Zhalsabilla; Andayani, Sari (International Journal of Multidisciplinary Research and Literature, 2023)
This study aims to find empirical evidence about taxpayer awareness's effect on motor vehicle tax compliance moderated by tax socialization. The population in this study are taxpayers of two-wheeled and four-wheeled motorized vehicles registered at the Bojonegoro SAMSAT Office reported in 2022. The sample used is part of the population. The models obtained were 100 respondents who were calculated using the Slovin formula. The data was collected in this study through surveys and questionnaires distributed to taxpayers at the SAMSAT and Google offices. The analysis technique uses the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach with the SmartPLS 4.0 software application. The results of this study indicate that taxpayer awareness has a significant influence on motor vehicle tax compliance. However, tax socialization weakens taxpayer awareness of taxpayer compliance